Crystal structure of 7-methoxy-1-[(E)-2,6-dimethylphenylimino] (phenyl)methyl-2-naphthol: Clarification of non-covalent bonding interactions on the basis of spatial organization of single molecular structure and the molecular alignments - Ogata, Kazuki; Nagasawa, Atsushi; Yonezawa, Noriyuki; Okamoto, Akiko (European Journal of Chemistry, 2017)
Crystal structure of the title compound, 7-methoxy-1-[(E)-2,6-dimethylphenylimino] (phenyl)methyl-2-naphthol, which has N-aryl group instead of ketonic carbonyl group has been comparatively analysed with the precursor compound of 1-benzoyl-2-hydroxy-7-methoxynaphthalene. The distinct features in the molecular accumulation structures of title triarylimine compound and the precursor diaryl ketone demonstrate that the spatial organization of the former is mainly determined π-π stacking interaction and for the latter the non-classical hydrogen bondings govern the spatial organization. Besides both of the compounds show non-coplanaryl accumulation of aromatic rings molecular structure, the title compound has molecular core of imino group which attaches three aromatic rings of C-1-naphthyl, C-phenyl, and N-phenyl stems of nearly perpendicular alignment of each aryl groups to residual two aryl ones respectively, giving highly congested circumstance at the inner site of molecules. On the other hand, the precursor aromatic ketone molecule has relatively large space compared to title compound, enabling conformational flexibility to some extent within restriction of maintaining non-coplanar organization. The molecules of the precursor compound in crystal are stabilized by a number of non-covalent bonding interactions, mainly by non-classical hydrogen bondings. The achievement stabilization contributed a number of non-classical hydrogen bonding is considered to be due to the inner-molecular motility of single molecular structure. Contrarily, the congested inner-molecular situation of title compound makes largely rigid molecular conformation, which affords at the same time exposure of three aromatic planes outside the molecular core. The single molecular organization permits π-π stacking interaction stabilization instead of formation of a number of weak interactions. Thus, the governing factors for the distinct feature of the single molecular and the accumulation structures of title compound and the precursor are interpreted from the viewpoint of predominantly effective intermolecular interaction, a strong π-π stacking interaction or sum of weak non-classical hydrogen bondings, determined by the inner-molecular congestive conditions directly affects the inner-molecular motility.